PENGARUH IKLIM ORGANISASI TERHADAP LOYALITAS KERJA KARYAWAN HOTEL BENTENG PEKANBARU - Indah Mustika Dewi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted at Hotel of Fortress Pekanbaru. This Research aim to toknow the organizational climate influence to loyalitas work the employees of Hotel of Fortress Pekanbaru. Organizational Climate as independent variable ( X) And loyalitas work as variable dependen ( Y). this research take the responder amount as much 45 people.In this research, data obtained use the koesioner with the scale penggukuran use the scale likert is later on processed and analysed to use the validity test, test the reliabilitas, analyse the statistic of like simple linear regression analysis, test the t, analyse the correlation and determinasi by using aid of application SPSS.Result of this research is result of hypothesis test the t, t calculate ( 6,410)> tables of ( 2,017). This matter is menunjukan that organizational climate have an in with the loyalitas work the employees. Where value of coefficient of determinasi menunjukan that intensive variable give the contribution to variable loyalitas work equal to 48,9% while the rest of equal to 51,1% influenced by other;dissimilar variable which is not discussed in this research.Keywords : Organizational climate, Loyalitas work , Organization chart